2015
DOI: 10.1111/dom.12528
|View full text |Cite
|
Sign up to set email alerts
|

Intensifying insulin regimen after basal insulin optimization in adults with type 2 diabetes: a 24‐week, randomized, open‐label trial comparing insulin glargine plus insulin glulisine with biphasic insulin aspart (LanScape)

Abstract: In long-standing type 2 diabetes with suboptimal glycaemia despite oral therapies and basal insulin, the basal plus regimen was non-inferior to biphasic insulin for biomedical outcomes, with a similar overall hypoglycaemia rate but more nocturnal events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
64
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 28 publications
2
64
0
2
Order By: Relevance
“…Similarly, the recently published GALAPA-GOS study demonstrated that in insulin-naive patients, premixed insulin once or twice daily reduced HbA 1c by a further 0.16 % (confidence interval 0.04 to 0.27) compared with insulin glargine with or without insulin glulisine [10]. Finally, in a subgroup analysis in insulin-naïve patients, premixed regimen had no difference with basal-bolus regimens (-0.15 %; -0.52 to 0.22) [11].For patients already on basal insulin, results from the LanScape study suggested that basal-plus regimens (glargine plus insulin glulisine once daily) are non-inferior to premixed insulin (biphasic insulin aspart 30 twice daily) in reducing HbA 1c [12]. However, a recent meta-analysis by Wang et al concluded that basal-bolus regimens have superior glycemic efficacy to premix insulin in non-insulinnaïve patients (-0.22 %; -0.42 to -0.02) [11].…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…Similarly, the recently published GALAPA-GOS study demonstrated that in insulin-naive patients, premixed insulin once or twice daily reduced HbA 1c by a further 0.16 % (confidence interval 0.04 to 0.27) compared with insulin glargine with or without insulin glulisine [10]. Finally, in a subgroup analysis in insulin-naïve patients, premixed regimen had no difference with basal-bolus regimens (-0.15 %; -0.52 to 0.22) [11].For patients already on basal insulin, results from the LanScape study suggested that basal-plus regimens (glargine plus insulin glulisine once daily) are non-inferior to premixed insulin (biphasic insulin aspart 30 twice daily) in reducing HbA 1c [12]. However, a recent meta-analysis by Wang et al concluded that basal-bolus regimens have superior glycemic efficacy to premix insulin in non-insulinnaïve patients (-0.22 %; -0.42 to -0.02) [11].…”
mentioning
confidence: 93%
“…Similarly, body weight increase in insulin-naive patients in the GALA-PAGOS trial was comparable between those randomized to insulin glargine with or without insulin glulisine once daily and those treated with a premixed insulin regimen once or twice daily (LS mean difference -0.3 kg; p = 0.12) [10]. Likewise, in the LanScape trial, there was no difference in weight gain between basal-plus and biphasic insulin regimens (-0.44 kg; -1.12 to 0.23) in patients inadequately controlled on basal insulin and oral antidiabetic agents [12]. These results are verified in the meta-analysis by Giugliano et al including both insulin-naive patients and patients already on insulin, verifying the lack of any significant difference in body weight change between premixed insulin and basal-bolus regimens based on results from nine studies (-0.21 kg; -0.61 to 0.19) [7].…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…23 in Eng et al [3]) demonstrated the superiority of basal insulin plus GLP-1-RA. At least two recent randomized controlled trials (4,5) had the specific aim to compare a basal-plus regimen with a twice-daily premixed insulin regimen in long-standing type 2 diabetes with suboptimal glycemia despite oral therapies and basal insulin: the basal-plus regimen was found to be noninferior (5) or inferior (4) to a premixed regimen in terms of reduction of HbA 1c and was associated with more nocturnal hypoglycemic events (5). The evidence so far produced indicates that the three options are at least equally effective and should have the same scientific dignity.…”
mentioning
confidence: 99%